Representasi Gus dalam Novel Romansa Islami di Platform Sastra Siber Fizzo - Fahmy, Zulfa; Nuryatin, Agus; Supriyanto, Teguh (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This research aims to determine the representation of the figure 'Gus' in Islamic romance novels on the Fizzo cyber literary platform. The phenomenon of Islamic romance novels that make 'Gus' the central character is increasingly widespread on the Fizzo cyber literary platform. Gus is a character created by the author with various characters that are different from reality. The research method used is qualitative, analyzing two novels, namely